2002
DOI: 10.1557/jmr.2002.0260
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Treatment on the Photocatalytic Activity of TiO2 Coatings for Photocatalytic Oxidation of Benzoic Acid

Abstract: The effects of thermal treatment on the properties and photoactivities of TiO2 catalysts supported on 316 stainless steel plates were examined. Degussa P-25 was immobilized on 316 stainless steel plates by electrophoretic deposition. These TiO2-coated plates were heated at 473, 673, and 873 K for 1 h. The photoactivities of these TiO2 coatings were determined based on the removal of benzoic acid as the model pollutant. In particular, the photoactivity decreased by 52% in the sample heated at 873 K compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 17 publications
1
15
0
1
Order By: Relevance
“…9 also shows that the amount of 4-CBA adsorbed on PPMSGF-50 films calcined at 550 • C is six times that of PPMSGF-50 films calcined at 600 • C. At the same time, the BET of PPMSGF-50 at 550 • C is 47.08 m 2 /g, approximately 1.5 times that of PPMSGF-50 calcined at 600 • C. Therefore, a remarkable increase in BET should be an important reason for the significant increase in the number of crystallites on which the 4-CBA can be adsorbed. As a result, the photocatalytic activity was significantly enhanced at 500 and 550 • C. In addition, previous studies have shown that transition metal ions function as electron-hole recombination centers, which lead to a decrease in photocatalytic activity [17,30,31]. Therefore, a remarkable decrease in the number of Cr 3+ on the surface of the films is most probably another important reason for the enhancement of photocatalytic activity at lower calcination temperatures.…”
Section: Effect On Strength Of Adhesion Of the Filmmentioning
confidence: 96%
“…9 also shows that the amount of 4-CBA adsorbed on PPMSGF-50 films calcined at 550 • C is six times that of PPMSGF-50 films calcined at 600 • C. At the same time, the BET of PPMSGF-50 at 550 • C is 47.08 m 2 /g, approximately 1.5 times that of PPMSGF-50 calcined at 600 • C. Therefore, a remarkable increase in BET should be an important reason for the significant increase in the number of crystallites on which the 4-CBA can be adsorbed. As a result, the photocatalytic activity was significantly enhanced at 500 and 550 • C. In addition, previous studies have shown that transition metal ions function as electron-hole recombination centers, which lead to a decrease in photocatalytic activity [17,30,31]. Therefore, a remarkable decrease in the number of Cr 3+ on the surface of the films is most probably another important reason for the enhancement of photocatalytic activity at lower calcination temperatures.…”
Section: Effect On Strength Of Adhesion Of the Filmmentioning
confidence: 96%
“…A common trend of increase in crystallite size both of anatase and rutile TiO 2 (see Table 2) occurs with the increase in calcination temperature for TiO 2 /diatomite composites, due to high frequency of aggregation and sintering among the grains. In this study, the rutile content in the supported catalysts can be calculated based on the intensities of the peaks for anatase and rutile in the XRD patterns as follows [28,29]:…”
Section: Crystalline Phase Studiesmentioning
confidence: 99%
“…This is important for the stainless steel mesh coating, since iron impurities caused by heating the steel could have a negative effect on the photocatalytic efficiency of the catalyst. It has been reported that Fe 3+ ions present in TiO 2 coated steel plates heated at 600°C and more, but not at lower temperatures (Chan et al, 2002).…”
Section: Characterization Of the Prepared Photocatalystsmentioning
confidence: 96%